Analysis Of Outpatient Satisfaction Level Of Clinical Pharmaceutical Services At Puskesmas Bungursari Tasikmalaya - fahmi sidiq; Rabiu Hamisu Kankarofi (Research Collaboration Community (RCC), 2023)
Pharmaceutical service agencies to carry out quality administration in the health sector. Quality administration must be seen, one of which is by checking the level of patient satisfaction. Patients are likely to be a broad and quality confirmation action in health services, which means that patient satisfaction must be an act that cannot be separated from the nature of health services. The motivation behind this research is to determine the level of short-term patient satisfaction with drug administration at the Bungursari Tasikmalaya Health Center. This examination is descriptive non-experimental by chance testing, sharing information using a survey. The results showed the level of short-term patient satisfaction with drug administration at the Bungursari Tasikmalaya Public Health Center pharmacy in all aspects with a level where the appearance aspect (Tangible) had a satisfaction level of 79.81% (satisfied), the empathy component (Empaty) had a typical satisfaction with a level of 79.63% (satisfied), the element of the satisfaction level of reliability (Reliability) has a satisfaction level of 79.44% (satisfied), the responsiveness component has a satisfaction level of 77.98% (satisfied) and the element of certainty (Assurance) has a typical patient satisfaction level of 81.46% (very satisfied). Considering the consequences of examining the level of outpatient patient satisfaction with pharmaceutical services at the Bungursari Tasikmalaya Health Center pharmacy installation with the Spearman Rank Test for each variable, each variable obtained a value less than 0.5, it can be concluded that there is a significant relationship between the quality of pharmaceutical services and patient satisfaction the road to services at the Bungursari Tasikmalaya Health Center.